1995
DOI: 10.1038/ng0695-135
|View full text |Cite
|
Sign up to set email alerts
|

Hyperproinsulinaemia in obese fat/fat mice associated with a carboxypeptidase E mutation which reduces enzyme activity

Abstract: Mice homozygous for the fat mutation develop obesity and hyperglycaemia that can be suppressed by treatment with exogenous insulin. The fat mutation maps to mouse chromosome 8, very close to the gene for carboxypeptidase E (Cpe), which encodes an enzyme (CPE) that processes prohormone intermediates such as proinsulin. We now demonstrate a defect in proinsulin processing associated with the virtual absence of CPE activity in extracts of fat/fat pancreatic islets and pituitaries. A single Ser202Pro mutation dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
420
1
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 633 publications
(450 citation statements)
references
References 35 publications
26
420
1
3
Order By: Relevance
“…2C), accounting for 46.3 Ϯ 2.4% of total proinsulin-and insulin-related radioactivity. The presence of such a secretory product in cells after 150 min is suggestive of its being stored in granules of the regulated pathway, given that no such storage compartment exists for the constitutive pathway but indicates unusually slow proinsulin conversion in keeping with published data (20). The other minor radioactive peaks could correspond to arginine-extended forms of insulin or other proinsulin conversion intermediates.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…2C), accounting for 46.3 Ϯ 2.4% of total proinsulin-and insulin-related radioactivity. The presence of such a secretory product in cells after 150 min is suggestive of its being stored in granules of the regulated pathway, given that no such storage compartment exists for the constitutive pathway but indicates unusually slow proinsulin conversion in keeping with published data (20). The other minor radioactive peaks could correspond to arginine-extended forms of insulin or other proinsulin conversion intermediates.…”
Section: Resultssupporting
confidence: 55%
“…The pancreatic ␤-cells of these mice are clearly granulated but the content of the granules appears to be less dense (20), suggesting storage of proinsulin instead of mature insulin. Despite this observation, it has been suggested that proinsulin fails to be targeted to the regulated pathway in ␤-cells of these mice and that CPE is the sorting receptor not only for POMC but for other prohormones including proinsulin itself (18,19).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Several mutations in mouse genes that lead to obesity have recently been characterized at the molecular level (1)(2)(3)(4)(5)(6)(7)(8). Further analysis of these genes and the use of mouse lines with mutations in these genes provides an opportunity to identify new therapeutic targets for the treatment of human obesity.…”
mentioning
confidence: 99%
“…Naggert et al [9] reported that mice homozygous for the fat mutation are obese and hyperglycemic. The mutation responsible for this phenotype was found in the CP-E gene.…”
Section: Introductionmentioning
confidence: 99%